1990
DOI: 10.1159/000261863
|View full text |Cite
|
Sign up to set email alerts
|

Do Voice Recordings Reveal whether a Person Is Intoxicated? A Case Study

Abstract: In this report we consider the possibility that speech analysis techniques may be used to determine whether an individual was intoxicated at the time that a voice recording was made, and discuss an analysis of the speech produced by the captain of the Exxon Valdez recorded at several points around the time of the accident at Prince William Sound, Alaska. A review of previous research on the effects of alcohol and other effects on speech production suggests that it may be possible to attribute a certain, unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…Pseudophonological (i.e., performance-related) effects (like coda devoicing) have been documented among populations other than children. Johnson, Pisoni, and Bernacki (1990) report on the intoxicated speech of the captain of the Exxon Valdez around the time of the accident at Prince William Sound, Alaska. They note, as do authors of other studies of intoxicated speech, that the realization of segments may be affected by intoxication.…”
Section: Arguments Against ''Child Phonology''mentioning
confidence: 99%
“…Pseudophonological (i.e., performance-related) effects (like coda devoicing) have been documented among populations other than children. Johnson, Pisoni, and Bernacki (1990) report on the intoxicated speech of the captain of the Exxon Valdez around the time of the accident at Prince William Sound, Alaska. They note, as do authors of other studies of intoxicated speech, that the realization of segments may be affected by intoxication.…”
Section: Arguments Against ''Child Phonology''mentioning
confidence: 99%
“…Klingholz, Penning, and Liebhardt (1988) examined the ability of an automated statistical program based on several objective measures of speech (e.g., fundamental frequency, signal‐to‐noise ratio) to classify 11 speakers at BAC levels from .05 to .15%. The authors reported high levels of accuracy (95–100%), but cautioned that these figures were dependent on having baseline measures, as individuals differed markedly.…”
Section: Behavioral/observable Indications Of Intoxicationmentioning
confidence: 99%
“…Johnson, Pisoni & Bernacki (1990) is an analysis of his speech while drunk.) (Hazelwood was captain of the oil tanker, the Exxon Valdez, which ran aground while he was drunk.…”
Section: A Preliminary Remark On Notationmentioning
confidence: 99%